Aggregation Methods in Group Decision Making: A Decade Survey - Wan Mohd, Wan Rosanisah; Abdullah, Lazim (Informatica, 2017)
A number of aggregation methods have been proposed to solve various multi-criteria decision making (MCDM) problems. In this work, we make a survey of the existing aggregation methods that have been used in various fields from 2006 until 2016. The information of the aggregation methods was retrieved from various academic databases and keywords that appeared in a number of international journals for a ten-year were gathered and analyzed. It is observed that eighteen over ninety five of journal articles or nineteen percent applied the Choquet integral to solving MCDM problem. This survey shows that this method is the most prominent compared to the other aggregation method. The result from observation provides a good indication to the researchers to extend the appropriate aggregation method in MCDM. It is suggested that the Choquet integral is the aggregation method that could be explored in future research due to its flexibility in handling interdependencies in criteria of MCDM.